2012
DOI: 10.1371/journal.pone.0031860
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function in Antarctic Nototheniids with ND6 Translocation

Abstract: Fish of the suborder Notothenioidei have successfully radiated into the Southern Ocean and today comprise the dominant fish sub-order in Antarctic waters in terms of biomass and species abundance. During evolution in the cold and stable Antarctic climate, the Antarctic lineage of notothenioids developed several unique physiological adaptations, which make them extremely vulnerable to the rapid warming of Antarctic waters currently observed. Only recently, a further phenomenon exclusive to notothenioid fish was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 101 publications
(145 reference statements)
6
46
1
Order By: Relevance
“…Complex-specific variability among species has also been documented in two other notothenioids (Mark et al 2012), but the state III rates reported for N coriiceps in our study are significantly higher than those found by Mark and coworkers (2012). In addition, our values are in close agreement to the variation in complex-specific contributions found in triplefin blennies (Hilton et al 2010).…”
Section: Antarctic Teleostscontrasting
confidence: 66%
See 4 more Smart Citations
“…Complex-specific variability among species has also been documented in two other notothenioids (Mark et al 2012), but the state III rates reported for N coriiceps in our study are significantly higher than those found by Mark and coworkers (2012). In addition, our values are in close agreement to the variation in complex-specific contributions found in triplefin blennies (Hilton et al 2010).…”
Section: Antarctic Teleostscontrasting
confidence: 66%
“…When extrapolated to 0°C, N. coriiceps liver mitochondria exhibited lower state III rates than observed in red muscle tissue of N. coriiceps and livers mitochondria of other notothenioids (Johnston et al 1994;Johnston et al 1998;Mark et al 2012). However, state III rates of the conspecifics L. squamifrons and L. nudifrons (Hardewig et al 1999a) were found to be significantly different.…”
Section: Antarctic Teleostsmentioning
confidence: 96%
See 3 more Smart Citations